Postharvest Life of Gladiolus grandiflorus L. cv. Jessica as Influenced by Pre-harvest Application of Gibberellic Acid and Kinetin - Kumar, Sunil; Gupta, A K (Journal of Postharvest Technology, 2014)
Effect of pre-harvest sprays of gibberellic acid and kinetin on postharvest life of gladiolus cv. Jessica was assessed. The field experiment was laid out in randomized block design, replicated thrice, with two levels of gibberellic acid (100 and 200 ppm) and kinetin (50 and,100ppm) by dipping the corms overnight and foliar spray during growth period. The laboratory experiment was laid out in completely randomized design, replicated thrice, with sucrose 4 percent and 8-HQC at 200ppm as vase solution to increase the postharvest life of cut flower. The plant growth regulators significantly enhanced the postharvest life of cut gladiolus spike.